The Effect of General Allocation Funds, Special Allocation Funds, Revenue Sharing Funds and Regional Expenditures on the Development of Districts/Cities of North Sumatra Province - Harahap, Parlinsyah; Erlina, Erlina; Sirojuzilam, Sirojuzilam (Budapest International Research and Critics University, 2021)
The objectives of this study are (1) to analyze the effect of the General Allocation Fund on the development of the Regency/City of North Sumatra Province. (2) Analyzing the influence of the Special Allocation Fund on the development of the Regency/City of North Sumatra Province. (3) Analyzing the effect of the Revenue Sharing Fund on the development of the Regency/City of North Sumatra Province. (4) Analyzing the influence of Regional Expenditures on the development of Regency/City of North Sumatra Province. (5) To analyze together the influence of the General Allocation Fund, Special Allocation Fund, Revenue Sharing Fund and Regional Expenditure on the development of the Regency/City of North Sumatra Province. The method of analysis can be grouped into quantitative data. The results of this study are (1) the General Allocation Fund (DAU) has a negative and insignificant effect on the development of districts/cities in North Sumatra Province, North Sumatra Province. (2) The Special Allocation Fund (DAK) has a negative and significant effect on the development of districts/cities in North Sumatra Province, North Sumatra Province. (3) Revenue Sharing Fund (DBH) has a positive and significant impact on the development of districts/cities in North Sumatra Province, North Sumatra Province. (4) Regional Expenditures (BD) have a positive and significant effect on the development of districts/cities of North Sumatra Province, North Sumatra Province. (5) DAU, DAK, DBH and Regional Expenditures simultaneously have a significant effect on the development of districts/cities in North Sumatra Province, North Sumatra Province.